Evidence for peripheral and central actions of codeine to dysregulate swallowing in the anesthetized cat - Bolser, Donald C.; Shen, Tabitha Y.; Musselwhite, M. Nicholas; Rose, Melanie J.; Hayes, John A.; Pitts, Teresa (Frontiers in Neurology, 2024)
Systemic administration of opioids has been associated with aspiration and swallow dysfunction in humans. We speculated that systemic administration of codeine would induce dysfunctional swallowing and that this effect would have a peripheral component. Experiments were conducted in spontaneously breathing, anesthetized cats. The animals were tracheotomized and electromyogram (EMG) electrodes were placed in upper airway and chest wall respiratory muscles for recording swallow related motor activity. The animals were allocated into three groups: vagal intact (VI), cervical vagotomy (CVx), and supra-nodose ganglion vagotomy (SNGx). A dose response to intravenous codeine was performed in each animal. Swallowing was elicited by injection of 3 mL of water into the oropharynx. The number of swallows after vehicle was significantly higher in the VI group than in SNGx. Codeine had no significant effect on the number of swallows induced by water in any of the groups. However, the magnitudes of water swallow-related EMGs of the thyropharyngeus muscle were significantly increased in the VI and CVx groups by 2–4 fold in a dose-related manner. In the CVx group, the geniohyoid muscle EMG during water swallows was significantly increased. There was a significant dose-related increase in spontaneous swallowing in each group from codeine. The spontaneous swallow number at the 10 mg/kg dose of codeine was significantly larger in the CVx group than that in the SNGx group. During water-evoked swallows, intravenous codeine increased upper airway motor drive in a dose-related manner, consistent with dysregulation. The data support the existence of both central and peripheral actions of codeine on spontaneous swallowing. At the highest dose of codeine, the reduced spontaneous swallow number in the SNGx group relative to CVx is consistent with a peripheral excitatory action of codeine either on pharyngeal/laryngeal receptors or in the nodose ganglion itself. The higher number of swallows in the CVx group than the VI group supports disinhibition of this behavior by elimination of inhibitory vagal sensory afferents.